Mammary disease in the male. - Pressa, Carlos; Laviña, Raúl; Albo, Manuel (Cirugía del Uruguay, 1987)
The male incidence in 2.300 cases of mammary disease consulls is analyzed by the authors. The incidence was 1,91 % . The method of study is also established, and non malignan! from malignan! processes are discrimina• ted. Is concluded that consulls are generally late, the rate of malignant disease is aboul 1 % and that prognosis is poor.